Diversity, correlation and path analysis in elite line of sesame (Sesamum indicum L.): DIVERSITY, CORRELATION AND PATH ANALYSIS IN ELITE LINE OF SESAME - DINKAR,; SIMA SINHA,; MANKESH KUMAR,; RAJIV KUMAR RANJAN,; ADITYA SHRI,; ABHIJEET KUMAR, (Journal of Oilseeds Research, 2025)
Sesame is one of the oldest and most highly nutritive oilseed crops, containing essential minerals, vitamins, phytosterols, tocopherols, lignans, and other nutritional or bioactive components that have a favorable impact on human health. Considering its health benefits, the demand for sesame is increasing. However, modern sesame cultivars often have a narrow genetic base due to domestication and selection. This narrowing of the genetic base makes it challenging to develop high-yielding varieties to meet the growing demand. Therefore, the current study was conducted on diversity, correlation, and path analysis involving 22 sesame genotypes and 14 yield and yield-attributing traits at Bihar Agricultural University, Sabour. All genotypes were grouped into five clusters, with Cluster III being the largest, comprising 10 genotypes. The maximum genetic distance was observed between the genotypes of Clusters I and IV. For improving seed yield per plant, genotypes from Cluster V can be used in hybridization programs, as they exhibit the highest yield values. Correlation analysis indicated that the number of branches per plant, number of capsules per plant, number of seeds per capsule, biological yield per plant, and harvest index showed a strong positive correlation with seed yield. In contrast, stem length to the first capsule had a strong negative correlation with seed yield. Therefore, indirect selection for these traits would be helpful in enhancing yield. Path analysis revealed that harvest index and biological yield per plant have a strong direct effect on yield and should be prioritized in yield improvement programs.